Disinterring the movement of traditional Malay kuih in Mersing, Johor towards viability of Malaysia’s heritage food - Kamaruzaman, Mohd Yusof (2022)
Food is an important and distinct heritage to different communities. Especially to Malaysia, its multiethnicity population bestowed with dynamic food heritage. The traditional Malay kuih for example, offers tremendous flavors, textures, and colors. Yet, numerous reports on its negligence in the local diet is increasing due to the globalization, standardization, and commodification of foreign influence in local heritage food. Despite that, this study aimed to explore the movement of traditional Malay kuih in Mersing, Johor for its persistent existence conferring viability. Accordingly, the understanding of this phenomenon guided with four research questions: 1) what is the meaning of traditional Malay kuih in Mersing?; 2)how does traditional Malay kuih produced in Mersing?; 3) how motivationsaffect to the production of traditional Malay kuih?; and 4) how can traditionalMalay kuih be a viable intangible heritage in Mersing? Qualitative research method with phenomenological case study approach was used as the study design. The traditional food product concept, Vroom’s expectancy theory and transactional communication model assemblage theorized the phenomenon. The primary data were gathered from in-depth interviews with experts of traditional Malay kuih in Mersing and supplementary data from focus group discussion (FGD) with the consumers also included. Data saturation point was achieved by the 21st informant. Audio-visual materials, participant observations, and document analysis were used for multiple triangulation strategies. Thematic analysis was performed with constant comparative technique to generate themes as answers to the research questions. Accordingly, the meaning of traditional Malay kuih in Mersing is analyzed to be construed by three characteristics namely: 1) the use of local crops as main ingredients; 2) major inculturation of East Coast traditions in product offerings; and 3) the mix of traditions from complex sub-ethnicities of Malay. Etiquettes of production are applied in the making of traditional Malay kuih including: 1) practicing the traditional Malay cooking methods; 2) enhancing traditional recipes’ formulation; 3) attuning affective technicality in the production; 4) optimizing attentiveness in clean production; and 5) maintaining the traditional Malay flavor. As the essence of the phenomenon, the structural meaning of traditional Malay kuih movement revealed motivational construction built upon: 1) receiving external supports for production; 2) admitting to the responsibility to preserve traditions; 3) committing to the sustenance of traditions; 4) utilizing potential business opportunities; and 5) attaining personal actualization. Lastly, the actual practices of the movement towards viability are normalized by: 1) strengthening the knowledge of traditional Malay kuih; 2) organizing kuih production systematically; 3) developing signature menu; 4) expanding business channels; and 5) strengthening mutual networking. This study revealed and documented an in-depth comprehension to the phenomenon of the traditional Malay kuih viability in Mersing as one of the Malay cultures and traditions in Malaysia’s food heritage. The affiliated transactional communication model with traditional food product concept and Vroom’s expectancy theory extended their uses within the heritage food viability context. It can help boosting the persistence of traditional Malay kuih production where entrepreneurs can benefit the movement that this research revealed. The persistent existence of the traditional Malay kuih equates to its viability which confers to sustainability. Aside all, the viability framework developed can also be used in similar subjects where viability is an issue towards sustaining the existence.